Hypertension and Hormone Mechanisms - Carey, Robert M.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2007)
Hypertension, a major risk factor for cardiovascular disease and stroke, is present in approximately one-quarter of the adult population of Western societies. Advances in the study and treatment of this condition are captured in this exceptionally important book. In Hypertension and Hormonal Mechanisms, distinguished panels of leading experts discuss new developments in hormones/autacoids related to hypertension. During the past decade, truly remarkable advances have been made in the identification of new components of the renin-angiotensin system. This book also provides the most up to date advancements in topics such as the importance of diabetes and obesity in hypertension and the new role of calcitonsin gene-related peptide (CGRP) in hypertension. Hypertension and Hormonal Mechanisms, written by the world’s experts in this field, aims to open new doors leading researchers closer to understanding the etiology and pathogenesis of primary (essential) hypertension, and to stimulate active research in the fundamental mechanisms of hypertension so that new therapies, and even prevention, can be realized in the not-too-distant future.
New Developments in the Renin-Angiotensin System -- The Intrarenal Renin-Angiotensin System -- Cardiac and Vascular Renin-Angiotensin Systems -- Regulation of Cardiovascular Control Mechanisms by Angiotensin-(1–7) and Angiotensin-Converting Enzyme 2 -- Angiotensin IV Binding Site -- Angiotensin AT2 Receptors in Blood Pressure Regulation -- Angiotensin II and Inflammation -- Aldosterone and Vascular Damage -- The Sympatho-Adrenal System in Hypertension II -- Neurogenic Human Hypertension -- Calcitonin Gene-Related Peptide and Hypertension -- The Renal Dopaminergic System, Hypertension, and Salt Sensitivity -- Metabolic Disorders and Hypertension -- Insulin Resistance and Hypertension -- Fatty Acids, Cell Signaling, and Cardiovascular Risk -- Goal-Oriented Hypertension Management in Diabetic and Nondiabetic Patients -- Endothelial Hormones and Autocoids in Hypertension -- Nitric Oxide and Hypertension -- Role of Endothelin-1 in Hypertension -- The Kallikrein-Kinin System and Hypertension -- Other Hormonal Systems and Hypertension -- Physiology of Natriuretic Peptides and Their Receptors -- Sex Steroids and Hypertension -- The Lipoxygenase System in the Vasculature and Hypertension.
Keywords: Endocrinology .; Internal medicine; Cardiology; Endocrinology; Internal Medicine; Cardiology